Biodiversidad de la selva baja caducifolia en un sustrato rocoso de origen volcánico en el centro del Estado de Veracruz, México - Castillo Campos, Gonzalo (Universidad Autónoma Metropolitana, 2003)
The study site is characterized by a rocky terrain of volcanic origin that resulted from a deposition of volcanic lava that occurred 10,000 years ago in the water catchments of the Rio Actopan found in the center of the state of Veracruz, Mexico. The area is located between latitude19º 31´ and 19º 37´ north, and 96º 41´ and 96º 54´ longitude west. The rocky landscape was divided in different units according to physical, biological, and land use characteristics. The characteristics that stand out are basalt lava, the crater of the monogenetic cineritic type, the steep slopes, the fluvial plains formed by the superficial rivers, the hills and a tilted plain. The objective of this research was to establish the alpha and gamma plant diversity, as well as the species turnover (beta diversity) among the low-stature deciduous forest and the secondary vegetation, in relation to the altitudinal gradient. The endemic plants were also identified, as well as the succulent flora found in the study site. For these, at each 100 m altitude, transects of 0.5 to 2.5 km long were established, transversal to the study site. Information was taken at 100 m2 quadrats for the arboreal and shrubby strata, and 4 m2 for the herbaceous one, at distances of 50 m each. At each quadrat herbarium specimens of the vascular plants were recorded and collected. Besides species cover, different environmental parameters were taken, such as slope, rockiness, altitude and mineral soil. Results show that the low-stature deciduous forest and secondary vegetation found at this volcanic terrain are highly rich species, having recorded 683 species, 395 genera, and 103 families of vascular plants. A high turnover of species was also found throughout the landscape. Also, the impact of human activity was found to be high, since about 70% of the original vegetation had been substituted by secondary vegetation. The latter was found to have caused a loss of species of the original vegetation that can barely colonize again the existent secondary habitats. Among the groups of families and species that were found to be more affected are pteridophytes, orchids, cacti, and bromeliads, which show certain specificity for these types of habitats. Also, most of the succulent flora, endemic species and woody plants native to primary forests that have also been affected. Diversity type of lowstature deciduous forest was found to be more then 50% registered for this type of vegetation in other areas of the center of central Veracruz. This rocky terrain is considered to concentrate the greatest percentage of endemic species per unit area for the region.; El área de estudio corresponde a un malpaís o sustrato rocoso volcánico que está delimitado por una corriente de lava, depositada hace 10,000 años, en el valle de la cuenca media alta del río Actopan en el centro del estado de Veracruz, México. Está localizada entre las coordenadas 19° 31’ y 19° 37’ de latitud norte y 96° 41’ y 96° 54’ de longitud oeste. Por sus características físicas, biológicas y de uso del suelo, la zona de estudio fue dividida en distintas unidades del paisaje. Entre estas últimas sobresalen el derrame de basalto, el cráter tipo cinerítico monogenético, los escarpes o acantilados, las planicies fluviales formadas por los ríos superficiales, el lomerío y la planicie inclinada. El objetivo principal de este trabajo fue determinar la diversidad vegetal alfa y gama, así como el recambio de especies (diversidad beta), entre la selva baja caducifolia y la vegetación secundaria en la zona estudiada, considerando el gradiente altitudinal que existe, así como identificar los elementos endémicos y la flora suculenta que se encuentra en la zona. Para cubrir estos objetivos se trazaron transectos de 0.5-2.5 km de longitud, a cada 100 m de altitud, transversales al flujo de la corriente de lava, donde se hicieron cuadros de 100 m² en el estrato arbóreo y arbustivo y de 4 m² en el herbáceo a intervalos de 50 m de distancia. En cada cuadro se registraron y colectaron especímenes de las diferentes especies de las plantas vasculares, que posteriormente fueron herborizados. Además de la cobertura de cada especie, se consideraron distintos parámetros ambientales como porcentaje de pendiente, rocosidad, sustrato desnudo y altitud. Como resultado de lo anterior, se encontró que la selva baja caducifolia y la vegetación secundaria desarrolladas en el malpaís, presentan 683 especies, 395 géneros y 103 familias de plantas vasculares. Asimismo, se presenta un alto recambio de especies. Por otra parte, la antropización, tiene efectos sobresalientes sobre la diversidad de la vegetación original, reemplazándola por una flora nómada o secundaria, en un 70% aproximadamente. Esta actividad ha ocasionando la pérdida de especies de la vegetación original que difícilmente pueden volver a colonizar los hábitats secundarios. Entre las familias y especies más afectadas se encuentran pteridofitas, orquídeas, cactáceas y bromeliáceas que presentan cierta especificidad por este tipo de hábitats y en general toda la flora suculenta, el endemismo y la flora leñosa propia de la vegetación primaria. La diversidad de la selva baja caducifolia superó hasta en un 50% a la registrada para este tipo de vegetación en otras áreas del centro del estado. Se considera que el malpaís de esta zona concentra el porcentaje por superficie más alto de especies endémicas para el estado de Veracruz.